2015
DOI: 10.1186/s12889-015-2425-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of narrative versus non-narrative information in school health education about alcohol drinking for low educated adolescents

Abstract: BackgroundTraditionally most health education materials are written in an expository non-narrative format. Scholars have argued that the effectiveness of materials may increase when these texts are replaced by narrative texts, and that the non-narrative texts should be replaced by narrative texts. However, no previous studies have tested these claims in the context of school health education for low educated adolescents. This study aims to do so for an existing preventive health education intervention about al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 38 publications
1
14
0
2
Order By: Relevance
“…17 Actually, children literature and storytelling have been proved to be effective in specifically conveying health knowledge: the persuasive effects of narrative engagement have been illustrated in many researches and reviews. [87][88][89][90][91][92][93][94][95] De Graaf et al have specifically performed a systematic review of 153 experimental studies on health-related narrative persuasion with a focus on the narrative characteristics as potential explanatory factors in the effectiveness to convey a health message. 87,88 The results showed that stories that presented a healthy behaviour were more often associated with effects on the intention to adopt it, and stories with high emotional content were usually more effective, as well as the use of a first or second-person perspective in the text.…”
Section: Efficacy Of Narrative-based Strategies To Promote Health Andmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Actually, children literature and storytelling have been proved to be effective in specifically conveying health knowledge: the persuasive effects of narrative engagement have been illustrated in many researches and reviews. [87][88][89][90][91][92][93][94][95] De Graaf et al have specifically performed a systematic review of 153 experimental studies on health-related narrative persuasion with a focus on the narrative characteristics as potential explanatory factors in the effectiveness to convey a health message. 87,88 The results showed that stories that presented a healthy behaviour were more often associated with effects on the intention to adopt it, and stories with high emotional content were usually more effective, as well as the use of a first or second-person perspective in the text.…”
Section: Efficacy Of Narrative-based Strategies To Promote Health Andmentioning
confidence: 99%
“…89 Zebregs et al included 15 studies that recorded positive persuasive effects of narrative. 91 Braddock and Dillard metanalyzed 74 studies that compared narrative-based interventions to a control group that did not receive any relevant message. 92 Their results showed that, compared to a baseline zero-effect, narrative had positive effects on story-consistent beliefs, attitudes and intentions.…”
Section: Efficacy Of Narrative-based Strategies To Promote Health Andmentioning
confidence: 99%
“…statistics) tends to engage cognitive processing and is reported to influence attitudes, whilst qualitative evidence (e.g. narrative), is processed affectively and has a stronger impact on behavioural intention [29,30]. Secondly, emotional appeals provoke affective responses, the use of fear or guilt to cause attitude change have been the most researched [12].…”
Section: Introductionmentioning
confidence: 99%
“…Son varios los científicos y expertos que realizan investigaciones de alcance experimental para medir la eficacia de la persuasión en mensajes narrativos utilizados en series de televisión, películas, textos, entre otros soportes (Hoeken & Sinkeldam, 2014;Hoeken, Kolthoff, & Sanders, 2016;Igartua & Vega, 2015;Zebregs, van den Putte, de Graaf, Lammers, & Neijens, 2015).…”
Section: Cómo Mejorar La Efectividad De Las Campañas Y Cómo Evaluarlaunclassified